Circadian clocks and energy metabolism - Sancar, Gencer; Brunner, Michael (Cellular and molecular life sciences, 2014)
Circadian clocks orchestrate behavioral and physiological processes in a time-of-day dependent manner. The network of clock-controlled genes is intimately interconnected with metabolic regulatory circuits. Circadian clocks rhythmically regulate the expression and activity of key metabolic players, which in turn feed back on the circadian machinery on the transcriptional and post-transcriptional level. Mutations of clock genes are often associated with metabolic defects, especially in lipid and glucose metabolism. Accumulating data suggest that the reciprocal coordination of circadian and metabolic pathways is crucial for cellular homeostasis and the health of the organism.
Gesehen am 21.08.2020